Technology and Language Revitalization in Indonesia: A Literature Review of Digital Tools for Preserving Endangered Languages - Meida Rabia Sihite; Berlin Sibarani (PT Inovasi Pratama Internasional, 2024)
This systematic literature review examines specific digital tools such as mobile apps, online dictionaries, and social media platforms, evaluating their implementation and effectiveness in preserving endangered languages in Indonesia. Drawing from an analysis of ten scholarly publications spanning 2019 to 2023, key tools identified include the Android-based Lampung dictionary,